Stress Fracture of the Supracondylar Process of the Humerus in a Professional Tennis Player. Issue 1 (January 2015) - Pedret, Carles; Balius, Ramon; Alomar, Xavier; Vilaró, Jaume; Ruiz-Cotorro, Angel; Minoves, Montserrat
Abstract : Abstract: The supracondylar process of the humerus is an anatomic variant present in 1% of the population associated with a fibrous band, the ligament of Struthers that attaches it to the medial epicondyle, and may serve as a proximal origin of a fascicle of the pronator teres. Fractures of the supracondylar process of the humerus are extremely rare. To the best of our knowledge, this is the first report of a stress fracture of the supracondylar process. We present the case of a professional tennis player with a stress fracture of the supracondylar process who underwent surgery to avoid possible displacement and neurovascular complications. Clinicians should consider the diagnosis of a supracondylar process fracture with or without neurovascular compression when examining athletes with otherwise unexplained arm or elbow pain. Stress fracture of the supracondylar process may be secondary to the excessive traction of the pronator teres.